Analisis Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Minum Obat Dan Pasien Penyakit Ginjal Kronis Yang Menjalani Hemodialisis Di Rsud Ahmad Yani Metro Lampung - Handika, Aida Fitri; Hidayaturahmah, Rizky; Angin, M Perangin (Journal of Islamic Medicine, 2022)
Background:Based on the 2010 Global Burden of Disease Study, CKD is in the 27th position as a global cause of death and is in the 18th position as the cause of death. Hemodialysis (dialysis) is a therapy that uses a machine instead of a kidney outside the body. Objectif : This study aims to analyze sociodemographic factors and clinical factors associated with medication adherence in CKD patients undergoing HD. Methods : This type of research is an observational study with a cross sectional design involving patients undergoing hemodialysis who have met the inclusion and exclusion criteria at the Ahmad Yani Hospital, Metro Lampung for the period March-April 2022. Data collection was carried out by direct interviews and looking at the patient's medical records. Medication adherence was measured using the MARS-5 questionnaire. The relationship between demographic factors and clinical factors on the level of adherence to medication was analyzed using bivariate analysis and linear regression analysis, while the relationship between the level of adherence to demographic and clinical factors used the Mann Whitney and Kruskal Wallis test. Results :Total respondents involved 89 patients, there is no relationship between demographic factors on medication adherence, but on clinical factors, namely the duration of hemodialysis and the amount of medication there is a relationship with medication adherence, the Assmp Sig value 0.05.  Conclusion : The level of compliance in this study, the low level has a greater value that is 67,4% and the high level is 42,6%.Keyword : Hypertension, drug interactions, outpatient